2021
DOI: 10.3329/jcamr.v8i1.52596
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic Pattern and Treatment Outcome after Completion of Induction Remission in Children with Acute Lymphoblastic Leukemia

Abstract: Background: Acute lymphoblastic leukemia (ALL) is presented with different immunophenotypic pattern. Objective: The purpose of the study was to evaluate the immunophenotypic pattern of ALL and also, to recognize the frequency of different ALL subtypes and treatment outcome after induction remission therapy. Methodology: This prospective study was conducted in the Department of Paediatric Hematology and Oncology at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from June 2017 to July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In our study, 1 child (8%) had T cell lineage and 92% patient was B cell lineage which is comparable to another Bangladeshi study where among 87 analyzed patients, 93.1% were B-cell ALL and 6.9% were Tcell ALL. 18 In our study the highest WBC count t50,000/ mm 3 was 42%. These counts were higher when compared to studies in the west but in concordance with studies from other Low-and Middle-income countries (LMIC), where baseline white blood cell (WBC) count of >50,000/mm 3 was seen in 23-37%.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In our study, 1 child (8%) had T cell lineage and 92% patient was B cell lineage which is comparable to another Bangladeshi study where among 87 analyzed patients, 93.1% were B-cell ALL and 6.9% were Tcell ALL. 18 In our study the highest WBC count t50,000/ mm 3 was 42%. These counts were higher when compared to studies in the west but in concordance with studies from other Low-and Middle-income countries (LMIC), where baseline white blood cell (WBC) count of >50,000/mm 3 was seen in 23-37%.…”
Section: Discussionsupporting
confidence: 50%
“…Diba F et al found in her study that most of the patients were 1 to 9 years of age (87.4%), which is almost similar to our study. 18 Sampagar A et al reported that male to female ratio of newly diagnosed ALL was 1.15:1. 19 In our study male to female ratio of newly diagnosed ALL was 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…Diba et al published their ALL study in Bangladesh (lower middle income -WB) involving 87 children aged 1-18 years that the cumulative mortality was found to be 29.9%, and the primary cause of death (22/26, 84.6%) was septicemia. [30] Infection is not just a problem of LICs. Although the mortality rate is low when examined in HIC, infection, and septicemia are still the number one cause among the causes of TRD.…”
Section: Discussionmentioning
confidence: 99%